ABOUT RESULTS TRUST MANAGEMENT OF PENSION SAVINGS BY GOVERNMENTAL MANAGEMENT COMPANY OF THE VNESHECONOMBANK FOR 2004-2017 - G. Fatkhlislamova; T. Gorbacheva (Вестник университета)
The structure and profitability of investment portfolios generated by the governmental management company of Vnesheconombank (GMC VEB) is investigated. Economic-mathematical method applied in the study made it possible to analyzes the structure and efficiency of investments in pension funds assets investment portfolios. The analysis of the market value of the investment portfolio of the GMC VEB, their structure and profitability. The article defines the major trends in the trust management of pension savings citizens by GMC VEB.